Shoe-leather costs in the euro area and the foreign demand for euro banknotes - Alessandro Calza; Andrea Zaghini (European Central Bank (ECB), 2015)
We estimate the shoe-leather costs of inflation in the euro area using monetary data adjusted for holdings of euro banknotes abroad. While we find evidence of marginally negative shoe-leather costs for very low levels of the nominal interest rate, our estimates suggest that the shoe-leather costs are non-negligible even for relatively moderate levels of anticipated inflation. We conclude that, despite the increased circulation of euro banknotes abroad, in the euro area the inflation tax is still predominantly borne by domestic agents, with transfers of resources from abroad remaining small.
Keywords: E41; C22; 330; currency abroad; euro; money demand; welfare cost of inflation